Complete recovery after complement factor I deficiency associated fulminant acute hemorrhagic leukoencephalitis: a case report - Szumutku, Fanni; Szabó, Léna; Liptai, Zoltán; Varga, Edit; Seszták, Tímea; Barsi, Péter; Goschler, Ádám; Szarvas, Gábor; Horváth, Klára; Nagy, Simon Péter; Prohászka, Zoltán; Szilágyi, Ágnes; et al. (Frontiers in Immunology, 2025)
IntroductionAcute hemorrhagic leukoencephalitis (AHLE) is a rare, fulminant neuroinflammatory disease with high mortality rate. It most often occurs after infections; however, the exact etiology of the disease remains unclear. We highlight that complement factor I (FI) deficiency may be a possible cause of AHLE.Case reportWe describe a 9-year-old patient presenting with fever, headache, dizziness, ataxia, and diplopia, who developed rapid neurologic decline and refractory intracranial pressure elevation. Based on clinical, laboratory, and MRI findings, AHLE was diagnosed. Successful treatment included therapeutic plasma exchange (PEX) and early decompressive craniectomy. At one year of follow-up, the patient showed complete recovery. Complement testing of the patient revealed complete FI deficiency. Genetic workup uncovered a germline pathogenic variant in the CFI gene.DiscussionAs AHLE is an emerging phenotype of complement FI deficiency, with only a few previously reported cases in the literature, high clinical suspicion and awareness among clinicians are needed. To control the complement system, prompt blockade with complement FI substitution via PEX and early decompressive craniectomy may be life-saving. In neuroinflammatory diseases with unknown etiology, complement testing is recommended.